The Mycobacterium phlei Genome: Expectations and Surprises - Das, Sarbashis (Oxford University Press, 2016)
Mycobacterium phlei, a nontuberculosis mycobacterial species, was first described in 1898–1899. We present the complete genome sequence for the M. phlei CCUG21000T type strain and the draft genomes for four additional strains. The genome size for all fiveis 5.3 Mb with 69.4% Guanine-Cytosine content. This is ≈0.35 Mbp smaller than the previously reported M. phlei RIVM draft genome. The size difference is attributed partly to large bacteriophage sequence fragments in the M. phlei RIVM genome. Comparative analysis revealed the following: 1) A CRISPR system similar to Type 1E (cas3) in M. phlei RIVM; 2) genes involved in polyamine metabolism and transport (potAD, potF) that are absent in other mycobacteria, and 3) strain-specific variations in the number of σ-factor genes. Moreover, M. phlei has as many as 82 mce (mammalian cell entry) homologs and many of the horizontally acquired genes in M. phlei are present in other environmental bacteria including mycobacteria that share similar habitat. Phylogenetic analysis based on 693 Mycobacterium core genes present in all complete mycobacterial genomes suggested that its closest neighbor is Mycobacterium smegmatis JS623 and Mycobacterium rhodesiae NBB3, while it is more distant to M. smegmatis mc2 155.